Characterization of Dynamic Gripping Force Feedback for Robot-Assisted Surgery - Schäfer Max B.; Riepe Sarah; Parenzan Matthias; Bauer Christian J. E.; Hotz Jonas; Meiringer Johannes G.; Weiland Sophie; Pott Peter P. (Current Directions in Biomedical Engineering)
Haptic feedback of gripping forces during robotassisted surgery can benefit the surgical outcome by means of reduced forces applied to the tissue. A custom-designed haptic user interface allows to control four degrees of freedom of the instrument’s endeffector and to display gripping forces. System-centered evaluation is performed to assess its capability of displaying feedback with high mechanical bandwidth. In addition, the perception of gripping forces is evaluated using task-centered methods. Two tasks were performed by ten participants to assess the perceived feedback regarding size and stiffness of grasped objects. Maximum feedback forces of 4.3N and a mechanical bandwidth of 73.5 Hz are achieved. Tests with participants showed promising results regarding the discrimination of size and stiffness of grasped objects.